A numerical, phenotypical and functional characterization of innate T cell populations in CVID - Arduini, Serena (Trinity College (Dublin, Ireland). Department of Immunology, 2016)
Common Variable Immunodeficiency (CVID) is a primary antibody deficiency characterized by widespread B cell defects, low serum immunoglobulin levels, recurrent infections and frequent idiopathic complications, including autoimmunity. Both comentional and innate T cells have previously been shown to provide help to B cells maturation and antibody production; innate T cell subsets are furthermore directly and indirectly involved in anti-microbial responses, and can participate in the regulation of inflammatory and autoimmune processes. We therefore followed B cell differentiation and investigated the phenotype and functions of innate T cell subsets in CVID patients with and without complications, aiming to define if these populations could play a role in CVID.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin, 2016